Free to choose? Differences in the hours determination of constrained and unconstrained workers - Mark L. Bryan (University of Essex, Institute for Social and Economic Research (ISER), 2002)
In individual surveys, large minorities of individuals typically report that they would like to change their weekly working hours at their current hourly wage. If this evidence reflects genuine constraints on individuals choice of hours, the determinants of hours should differ between constrained and unconstrained groups. Controlling for selection by an extension of the Heckman two-step method to ordered selection and panel data, and using a sample of manual men, I find that unconstrained workers hours are determined differently from those of constrained workers. I present evidence that local labour market conditions affect the hours of constrained but not of unconstrained workers. I also correct for the potential bias resulting from the use of observed hours to derive the hourly wage, by instrumenting it with its lagged value. The combination of ignoring hours constraints and assuming the derived hourly wage is exogenous imparts a large downward bias to estimates of the wage elasticity. I estimate the corrected uncompensated elasticity to be -0.1.
Keywords: 330